Analyzing the role of CagV, a VirB8 homolog of the type IV secretion system of Helicobacter pylori - Navin Kumar; Mohd Shariq; Amarjeet Kumar; Rajesh Kumari; Naidu Subbarao; Rakesh K. Tyagi; Gauranga Mukhopadhyay (FEBS Open Bio, 2017)
The type IV secretion system of Helicobacter pylori (Cag‐T4SS) is composed of ~ 27 components including a VirB8 homolog, CagV. We have characterized CagV and reported that it is an inner membrane protein and, like VirB8, forms a homodimer. Its stability is not dependent on the other Cag components and the absence of cagV affects the stability of only CagI, a protein involved in pilus formation. CagV is not required for the stability and localization of outer membrane subcomplex proteins, but interacts with them through CagX. It also interacts with the inner membrane‐associated components, CagF and CagZ, and is required for the surface localization of CagA. The results of this study might help in deciphering the mechanistic contributions of CagV in the Cag‐T4SS biogenesis and function.